DETERMINATION OF RENAL RESISTIVITY INDEX IN PATIENTS HAVING TYPE II DIABETES MELLITUS - Tahir, Sadia; Shafique, Mobeen; Ali, Dilshad; Khan, Muhammad Babar; Sadiq, Tehmina; Rehman, Hina (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine mean renal resistivity index using renal artery Doppler in patients having type 2 diabetes mellitus.Study Design: Cross-sectional study.Place and Duration of Study: Armed Forces Institute of Radiology and Imaging Rawalpindi, from Jan 2016 to Jul 2016. Methodology: One hundred and fifty patients diagnosed with Type II Diabetes mellitus were included in this study. Renal resistivity index of both the kidneys at the level of segmental arteries was measured through color Doppler system (SSA-580A Toshiba, Japan) equipped with a transducer 3.75 MHz. At least two readings taken each at upper, mid and lower pole and average resistivity index was calculated. HbA1c levels were carried out through standard lab procedures.Results: Mean age of the patients was 54.06 ± 8.27 years. Out of 150 cases, 87 patients (58.0%) were male and 63 patients (42.0%) were female. Mean duration of diabetes was 5.53 ± 2.22 years. Mean HbA1c was 7.58 ± 1.02. Mean renal resistivity index of right kidney was 0.72 ± 0.02, mean renal resistivity index of left kidney was 0.72 ± 0.03 and average of both kidneys’ mean renal resistivity index value was 0.72 ± 0.02. Conclusion: Renal resistivity indices were high in patients with type 2 diabetes. This signifies that renal Doppler ultrasounds may be used as a non-invasive marker to identify patients with diabetes who have high risk of developing early nephropathy and thus may contribute to timely diagnosis and control disease progression.